Comparative profitability analysis of shifting land from field crops to mango cultivation in selected areas of Bangladesh - Khandoker, S; Miah, MA Monayem; Rashid, MA; Khatun, M; Kundu, ND (Bangladesh Journal of Agricultural Research, 2017)
Mango has emerged as an important area for diversification and as an alternative cropping pattern due to higher returns and productivity. The study was conducted in three mango growing districts, namely Chapai Nawabganj, Natore, and Rajshahi during 2014-2015 to estimate the financial benefit of shifting cereal lands to mango production, factors influencing shifting decision, and explore related problems of mango cultivation in the study areas. A total of 180 farmers taking 60 farmers from each district were selected through using multistage stratified random sampling for the study. About 49% lands were shifted to mango cultivation from cereal crops which was higher in Chapai Nawabganj (55%) followed by Natore (48%) district. The main reason of this shifting was reported to be higher profit compared to other crops. The average total cost of mango cultivation was Tk. 1, 33,889 per hectare. Higher cost was observed in the 16th-20th year of garden (Tk. 1, 52,010) followed by 11th -15th year (Tk. 1, 48,952). The average yield of mango was found to be the highest in 16th 20th year (26.48 ton/ha) followed by 11-16th year (19.38 ton/ha). Per hectare net return from mango cultivation was Tk. 1, 75,244. Total cost of mango cultivation was 10% higher than Boro-Fallow-T.Aman cultivation. On the other hand, total cost was about 40% lower than Wheat- Jute- T.Aman, Wheat-Aus-T.Aman and Potato-Fallow-T.Aman. The net return from mango cultivation was 75% higher than other cropping patterns. The shifting of cereal lands to mango cultivation was found to be a profitable since the BCR (2.89), net present value (Tk. 33, 71,166) and internal rate of return (39%) were very high. Relative income, farm size and education turned out to be positively significant, whereas age was negatively significant for shifting decision from cereal crops to mango cultivation. Therefore, Farmers should be motivated to cultivate mango in the fallow lands or areas where other crops are not grown well. Bangladesh J. Agril. Res. 42(1): 137-158, March 2017